Functional role of connexin 46 in lens epithelial cell differentiation and growth - Madgwick, Daniel (Kansas State University, 2008)
The vertebrate lens relies on gap junction-mediated intercellular communication to maintain cellular homeostasis and lenticular transparency. Differentiation of cuboidal lens epithelial cells into cortical fiber cells involves the degradation of endogenous gap junction protein, connexin 43 (Cx43) and the up-regulation of connexin 46 (Cx46). Cx46 may also be involved in the hypoxia response in other tissues; a function that can possibly be attributed to unique phosphorylation sites at the cytoplasmic C-terminus. In this study, we have developed a mammalian (rabbit) lens epithelial cell (RLEC) culture model that overexpresses Cx46 to ascertain the role of Cx46 in differentiation and oxidative stress response. The cell line N/N1003A was stably transfected with a GFPCx46 plasmid construct, and analyzed for differentiation markers including endogenous gap junction protein isoforms (Cx43 and Cx50). Western blot analysis and visual observation determined that the stable overexpression of Cx46 (sCx46OE) induced the degradation of Cx43 and elicited morphological changes indicative of fiber cell elongation. Total RNA from RLEC culture was isolated and analyzed for mRNA levels using RT-PCR. Comparable levels of Cx43 transcript were present in wild type, transient Cx46OE (tCx46OE), and sCx46OE which suggests a post-transcriptional regulation of Cx43 degradation. Treatment of sCx46OE with proteasome inhibitors restored Cx43 protein levels, and scanning confocal microscopy supported our hypothesis that Cx43 is degraded in differentiating lens cells by way of a ubiquitinmediated proteasomal pathway. It is our conclusion that Cx46 has application in hypoxic conditioning and differentiation in addition to its conventional role as a gap junction protein.
Keywords: Gap junctions; Lens; Cx46; differentiation; Biology, Molecular (0307)